2019
DOI: 10.1021/acsmedchemlett.8b00484
|View full text |Cite
|
Sign up to set email alerts
|

Bioisosteres of Indomethacin as Inhibitors of Aldo-Keto Reductase 1C3

Abstract: Aldo-keto reductase 1C3 (AKR1C3) is an attractive target in drug design for its role in resistance to anticancer therapy. Several nonsteroidal anti-inflammatory drugs such as indomethacin are known to inhibit AKR1C3 in a nonselective manner because of COX-off target effects. Here we designed two indomethacin analogues by proposing a bioisosteric connection between the indomethacin carboxylic acid function and either hydroxyfurazan or hydroxy triazole rings. Both compounds were found to target AKR1C3 in a selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 30 publications
(74 reference statements)
0
25
0
Order By: Relevance
“…Liu et al, 24 have reported that resistance to antiandrogens can be overcome in vitro and in vivo by using the AKR1C3 inhibitor indomethacin, an NSAID with limited use due to gastrointestinal toxicities. Several high‐throughput screening campaigns have identified novel chemical matter that is more potent and selective for AKR1C3 as well as more tolerable than indomethacin 26‐29 . AKR1C3 is a multifunctional enzyme with catalytic‐dependent and independent functions that drive AR signaling activity 20,30 .…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al, 24 have reported that resistance to antiandrogens can be overcome in vitro and in vivo by using the AKR1C3 inhibitor indomethacin, an NSAID with limited use due to gastrointestinal toxicities. Several high‐throughput screening campaigns have identified novel chemical matter that is more potent and selective for AKR1C3 as well as more tolerable than indomethacin 26‐29 . AKR1C3 is a multifunctional enzyme with catalytic‐dependent and independent functions that drive AR signaling activity 20,30 .…”
Section: Discussionmentioning
confidence: 99%
“…Most of the strong predictions from BHC were known bioactive compounds or even drugs. Morphine, for example, was predicted to bind opioid receptors (delta, kappa, or mu), (Cahill et al, 2001) ursolic acid was associated with protein-tyrosine phosphatase 1B, (Zhang et al, 2006) atropine sulfate with muscarinic acetylcholine receptors M2 and M3, (Paton and Rang, 1965) indomethacin with cyclooxygenase and aldo-keto reductase family 1 member C3, (Lolli et al, 2019) estradiol with estrogen receptor and stearyl sulfatase, (Reed et al, 2005) etc. Diclofenac was associated with interleukins, which induce the activity of its target cyclooxygenase-2.…”
Section: Figmentioning
confidence: 99%
“…[30] Therefore, AKR1C3 is considered to be a vital therapeutic target in the treatment of CRPC through suppressing the final steps of intratumoral production of androgen. [27] Numerous AKR1C3 inhibitors with diverse scaffolds have been investigated for their enzyme inhibitory activity, such as steroids, [24] flavones, [31] jasmonates, [32] nonsteroidal anti-inflammatory drugs (NSAIDs, including Indomethacin analogs, [33,34] diarylpropionic acids, [35] and benzoic acid derivatives [36][37][38][39][40] ), cinnamic acid derivatives, [41] and some miscellaneous (SN33638, [42] ASP9521, [43] GTX-560, [30] morpholyl urea derivatives, [44] hydroxytriazole derivatives, [45] benzisoxazole derivatives, [46] berberine, [47] pyrazolopyran, [48] sulfonylureas [49] ). However, no specific AKR1C3 inhibitor has been successfully marketed.…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy of Indomethacin in combination with enzalutamide in CRPC is still ongoing [50] . Many reports show that indole derivatives occur widespread in biologically active compounds such as pharmaceuticals, agrochemicals and alkaloids, and indole scaffold is a popular component of fragrances and the precursors of many antitumor pharmaceuticals, [51] like those indole‐based AKR1C3 inhibitors mentioned above ( Scheme 1), such as Indomethacin ( A , IC 50 =0.1 μ M ), [33] Indomethacin sulfonamide analog ( B , IC 50 =0.34 μ M ), [33] Indomethacin hydroxytriazole analog ( C , IC 50 =0.30 μM), [34] and ASP9521 ( D , IC 50 =0.12 μ M ) [43] . On the other hand, through analyzing the structure of the currently reported well‐active AKR1C3 small molecule inhibitors, we found many of them had a carboxy group as a pharmacophore, especially benzoic acid fragment ( Scheme 1), such as Flufenamic acid analogs ( E , IC 50 =0.035–0.86 μ M ), [36,40] N ‐naphthylaminobenzoic acid ( F , IC 50 =0.08 μ M ), [38] compound G (IC 50 =0.31–0.35 μ M ), [39] and compound H (IC 50 =0.006 μ M ) [37] .…”
Section: Introductionmentioning
confidence: 99%